1971
DOI: 10.1073/pnas.68.10.2458
|View full text |Cite
|
Sign up to set email alerts
|

Control of Single Ribosome Formation by an Initiation Factor for Protein Synthesis

Abstract: ABSTRACT30 and 50S ribosomal subunits, released from polysomes upon polypeptide chain termination, possess a high affinity for each other and readily form single ribosomes. Highly purified initiation factor F3(B), acting stoichiometrically, prevents the formation of single ribosomes without promoting their dissociation. These findings are interpreted in terms of a ribosome cycle in which a limiting amount of factor F3(B) controls the number of ribosomes active in protein synthesis, in response to metabolic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Recent studies have shown that IF-3 acts as antiassociation factor since the equilibrium between 70 S ribosomes and 50 S and 30 S ribosomal subunits is shifted in favour of the subunits by the binding of IF-3 to free 30 S particles [3][4][5]. The finding that IF-3 does not stably bind to the 70 S monomers is consistent with this scheme [6][7][8].…”
Section: Introductionsupporting
confidence: 55%
“…Recent studies have shown that IF-3 acts as antiassociation factor since the equilibrium between 70 S ribosomes and 50 S and 30 S ribosomal subunits is shifted in favour of the subunits by the binding of IF-3 to free 30 S particles [3][4][5]. The finding that IF-3 does not stably bind to the 70 S monomers is consistent with this scheme [6][7][8].…”
Section: Introductionsupporting
confidence: 55%
“…Perhaps the axoplasmic flow has been temporarily stemmed, perhaps a preceding surge in synthesis has exhausted the supply of substrates, mRNA, or initiation factors. Kaempfer (15) suggested that the balance between a critical initiation factor like IF-3, which is usually in short supply, and the ribosomal subunits could provide a mechanism for the control of the number of active ribosomes and thus of protein synthesis. Whatever the reason, it would appear likely that the suspension of protein synthesis is a phase in the cyclic function of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, if an underproduction of 40-S subunits does indeed occur, then the level of free active 40-S anti-association factor (in the cytoplasm) may be higher than normal. Previous studies [27] have demonstrated that frequent subunit exchange takes place iz7 vivo between 80-S free couples and native subunit pools (presumably through exchange of anti-association factor) so it should be possible to generate a normal complement of native 40-S subunits in CLP-8 by increasing the amount of 80-S free couples. Accordingly, intact spheroplasts from both CLP-8 and A224A were incubated for 15 min at 30 'C in the presence of sodium azide (1 mM).…”
Section: Resultsmentioning
confidence: 99%
“…In growing yeast cells frequent subunit exchange occurs between 80-S free couples and the native ribosomal subunit pool with no evidence of a fraction of 80-S ribosomes unable to dissociate or for accumulation of subunits incapable of recycling [27]. To ascertain if the native 60-s* peak of CLP-8 is functionally homogeneous and capable of such recycling we developed an assay system for protein synthesis in vitro utilizing either high-salt-washed 80-S ribosomes or purified ribosomal subunits, a crude factor preparation and exogenous mRNA, i.e.…”
Section: Resultsmentioning
confidence: 99%